Kenyan NFD Muslim communities : the painful past and pending justice - Sheikh Alio, Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2022)
The political history of Muslim minorities in the world is one of the emerging areas in the Muslim world’s contemporary issues that need to be addressed. This research examines the political history of Muslim communities in Kenya’s former Northern Frontier District (NFD), which was part of Somali Jubaland but annexed to Kenya Colony by British authorities in 1925, and the challenges they confronted during British colony (1895-1963); in terms of isolation measures, political marginalization and disregarding the 1962 referendum which expressed their will to unite with Somalia. Furthermore, the study discloses the harder difficulties that encountered NFD natives after Kenya independence in 1963; which appeared through the Shifta War (1963-1967), human rights violations, chronic marginalization and pending justice over historical grievances. The research will contribute to discovering the political and social history of Muslim communities in NFD and its impact on the current situation of former NFD’s residents in Kenya towards gaining a long-lasting stability in Kenya.